Temporal consistency of ontogenetic shifts in habitat use by coral reef fishes in the northernmost coral ecosystem in the world (Kudaka Island, Japan) - D. Lecchini; M. Tsuchiya (Journal of Fish Biology, 2008)
The prevalence of major habitat shifts in tropical fishes between juvenile and adult stages (ontogenetic shifts) in one of the northernmost coral reefs in the world (Kudaka Island, Japan) is given. The comparative analysis of spatial distribution of juveniles v . adults highlighted four ontogenetic patterns: no change in habitat use between juveniles and adults (five species), a decrease in the number of habitats used by adults compared to juveniles (three species), an increase in the number of habitats used during the adult stage (four species) and use of nursery areas by juveniles followed by extensive movements to different adult habitats (three species). The comparative analysis of fish distribution over time ( i.e. during three consecutive settlement months) showed that 84% of species had temporal consistency in ontogenetic patterns of habitat use.